Entrepreneurial evangelical ecclesiology : towards a critical evaluation of the Willow Creek seeker-sensitive model - Cameron, Alan Duncan (Stellenbosch : Stellenbosch University, 2012)
Thesis (MTh)--Stellenbosch University, 2001.